An over-110-GHz InP HEMT flip-chip distributed baseband amplifier with inverted microstrip line structure for optical transmission system. - Masuda, S. (IEEE Journal of solid state circuits)
We successfully developed state-of-the-art InP high electron mobility transistor (HEMT) distributed amplifiers by using inverted microstrip line (IMSL) technology. The IMSL has minor frequency dispersion characteristics and a simple equivalent circuit model can embody its discontinuity, such as a T-junction, because it has a large ground plane at the surface of the chip. For one distributed amplifier, we achieved a gain of 14.5 dB and a 94-GHz 3-dB bandwidth resulting in a gain-bandwidth product of 500 GHz, and for the other we achieved a gain of 7.5 dB and a 3-dB bandwidth of over 110 GHz. Furthermore, this technology also offers the capability of fabricating ultra-broad-band packaged ICs with flip-chip assembly for operation up to the W-band. In this paper, we focus on the advantage of IMSL technology for circuit design. We used an IMSL structure to design and fabricate a distributed amplifier to verify the advantages of IMSL. Our results show that this is an accurate technique for designing broad-band circuits up to 110 GHz.